The application of stable isotope ratio analysis to determine the geographical origin of wheat. (1st May 2015) - Luo, Donghui; Dong, Hao; Luo, Haiying; Xian, Yanping; Wan, Juan; Guo, Xindong; Wu, Yuluan
Highlights: We used EA–IRMS to determine not only δ 13 C value, but also δ 15 N value of wheat. Wheat originated from Australia, the USA, Canada and China could be discriminated by EA–IRMS. The regional distributions of 5 origins of wheat were clearly illustrated in a box plot and a cross plot. Abstract: In this work, in order to discriminate the geographical origin of wheat, δ 13 C and δ 15 N values of 35 wheat samples originated from different regions were determined, using the method of element analyser–stable isotope ratio mass spectrometry. The results indicated that wheat from Australia, the USA, Canada and China could be potentially discriminated by using analyte δ 13 C and δ 15 N. δ 13 C values of wheat were ranged from −25.647‰ to −22.326‰, the δ 15 N values of 35 wheat samples were calculated between 1.859‰ and 7.712‰. Moreover, the results illustrated regional distributions of δ 15 N values of wheat as Australia > The USA > Jiangsu province of China > Shandong province of China > Canada. So δ 13 C and δ 15 N analysis would be potentially useful for rapid and routine analyses of geographical origin of wheat, even the cereal grains. In order to confirm the discrimination capability of δ 13 C and δ 15 N, a follow-up work will use this method to analyse a larger set of samples.